2012
DOI: 10.1111/j.1365-2966.2012.20562.x
|View full text |Cite
|
Sign up to set email alerts
|

Modelling injection and feedback of cosmic rays in grid-based cosmological simulations: effects on cluster outskirts

Abstract: We present a numerical scheme, implemented in the cosmological adaptive mesh refinement code enzo, to model the injection of cosmic ray (CR) particles at shocks, their advection and their dynamical feedback on thermal baryonic gas. We give a description of the algorithms and show their tests against analytical and idealized one‐dimensional problems. Our implementation is able to track the injection of CR energy, the spatial advection of CR energy and its feedback on the thermal gas in run‐time. This method is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
69
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 102 publications
(230 reference statements)
6
69
0
Order By: Relevance
“…Disc-shaped shock fronts with a cylindrical wake can be seen in hydrodynamical simulations of cluster mergers (e.g. Vazza et al 2012) and provide a simple yet realistic model for deprojecting the Planck y-map.…”
Section: Discussionmentioning
confidence: 99%
“…Disc-shaped shock fronts with a cylindrical wake can be seen in hydrodynamical simulations of cluster mergers (e.g. Vazza et al 2012) and provide a simple yet realistic model for deprojecting the Planck y-map.…”
Section: Discussionmentioning
confidence: 99%
“…The generation can be taken into account in the CR MHD equations, if it is modelled successfully (see e.g. Zank et al 1993;Jubelgas et al 2008;Vazza et al 2012). Thus far, only the energy injection rate, is taken into account in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Bykov 2014), and cosmological structure formation through shocks (see e.g. Pfrommer et al 2006;Vazza et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Pfrommer et al (2007) and Vazza et al (2012), adopting specific DSA efficiency models, showed that the CR acceleration occurs mostly in the cluster outskirts. Because of long lifetime and slow particle diffusion (e.g., Berezinsky et al 1997), the CR protons accelerated in the outskirts are likely to be contained in clusters and accumulated in the ICM over cosmological timescales.…”
mentioning
confidence: 99%
“…In some simulations for the LSS formation, the injection/ acceleration of CR protons at shocks and the spatial advection of the CR pressure were followed self-consistently in runtime (e.g., Miniati et al 2001;Pfrommer et al 2007;Vazza et al 2012). Pfrommer et al (2007) and Vazza et al (2012), adopting specific DSA efficiency models, showed that the CR acceleration occurs mostly in the cluster outskirts.…”
mentioning
confidence: 99%